2020
DOI: 10.1101/2020.08.20.259671
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanisms of signalling-memory governing progression through the eukaryotic cell cycle

Abstract: As cells pass through each replication-division cycle, they must be able to postpone further progression if they detect any threats to genome integrity, such as DNA damage or misaligned chromosomes. Once a decision is made to proceed, the cell unequivocally enters into a qualitatively different biochemical state, which makes the transitions from one cell cycle phase to the next switch-like and irreversible. Each transition is governed by a unique signalling network; nonetheless, they share a common characteris… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…This transition is characterized by the establishment of gap phases and slowing down of the cell cycle, resulting in a higher resemblance to the cell cycle as typically studied in yeast and mammalian somatic cells. Remarkably, many of the transitions between these additional cell cycle phases are—just like the G2-M transition—governed by bistable switches [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This transition is characterized by the establishment of gap phases and slowing down of the cell cycle, resulting in a higher resemblance to the cell cycle as typically studied in yeast and mammalian somatic cells. Remarkably, many of the transitions between these additional cell cycle phases are—just like the G2-M transition—governed by bistable switches [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Once these are correctly attached, the cohesin rings that are keeping the sister chromatids together can be cleaved, upon which the chromatids are separated by the mitotic spindle. Although some experimental studies question the all-or-none nature of the SAC [ 21 , 22 ], indirect experimental and theoretical findings support the idea that this transition is also centered around a bistable switch [ 23 26 ]. Given the recurring occurrence of all-or-none transitions throughout the cell cycle, the latter has been envisioned as a chain of interlinked bistable switches ( Fig 1B ) [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…On another note, a recent study suggested that CycD/Cdk4,6 mono-phosphorylates but does not inhibit Rb, and it meanwhile activates CycE/Cdk2 via an unidentified mechanism [54]. Although this new finding and the classic model differ in whether CycD/Cdk4,6 directly inhibits Rb, they are consistent in the role of CycD/Cdk4,6 in leading to CycE/Cdk2 activation and initiating the positive mutual-inhibition loop between Rb and E2f, which eventually leads to E2f activation and the passage of the restriction point during the quiescence-to-proliferation transition [55][56][57][58][59][60].…”
Section: Discussionmentioning
confidence: 79%
“…This process is governed by the orderly progression through different phases of the cell cycle. The eukaryotic cell cycle contains various checkpoints and transitions in which bistability plays a role ( Fig 1C), and can even be viewed as a chain of sequentially activated bistable switches [16][17][18][19]. These switches provide robustness and directionality to the cell cycle and ensure the genome's integrity.…”
Section: Introductionmentioning
confidence: 99%